(untitled) (Informatica, 2024)
With the advancement of communications technologies and hardware technologies, animation creation can only continue to innovate to keep up with the times. Special education has recently shown considerable interest in animations. Novel types of presentations, such as animations, multimedia, and virtual reality, have been made available by technological advances in teaching. A significant mainstream media, communications, and education platform is animation software. There has been a rise in both the diversity and the rate of creation of new cartoon products because of the development of new techniques and the accumulation of new information. In this research, we suggest a virtual reality system based on a predictive correction method (VR-PCM). The widespread adoption and implementation of virtual reality (VR) based on predictive correction method (VR-PCM) technology has prompted researchers to examine VR-potential PCM’s impact on the field of animation education. To carry out the design of the lessons themselves, the existing VR technologies are merged to carry out teaching, including a multitude of environmental modeling, real-time 3D graphic production, simultaneous display, and sensor technology. Research on these four facets of the major-teaching process has been conducted in light of the present state of affairs. When paired with a 3D animation course, VR-PCM technology may be utilized to enhance the effectiveness of instruction for classes focused on professional skills. Finally, in the practical implications section, we evaluate and contrast the impact of various pedagogical strategies, including student feedback, overall quality assessment, and professionals’ core curriculum. Students in the VR technology group showed considerable improvement in their overall quality assessments.